Design and Simulation of E shape L slot Microstrip Patch Antenna with different substrates for Wireless Communication - Gyanender Kumar, Harmeet Singh Gill , Priyanshu Tripathi, (International Journal of Scientific Research and Management (IJSRM), 2014)
The area of microstrip antennas has seen some inventive work in recent years and is one of the most dynamic fields of antenna theory. In this paper we have proposed configuration of patch antenna having E shape L slot patch. Performance of patch antenna is characterized by return loss & gain. Different substrates are used to get an improved gain and return loss.